2023
DOI: 10.21660/2023.102.g12141
|View full text |Cite
|
Sign up to set email alerts
|

Soil Behavior Modeling by MPS-Cae Simulation

Abstract: Many numerical simulation methods have been developed in the current research field. The authenticity of the simulation-based research depends on the accuracy of the model prepared. The modeling of the soil becomes challenging when there is the presence of water and the soil starts behaving like a fluid. This study focuses on the application of the MPS (moving particle semi-implicit) -CAE (computer-aided engineering) method to design the setup for the unconfined compression test to determine the correct parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…Next, to deduce the relationship between plastic viscosity and the yield value, it is important to notice the relation between plastic viscosity and the unconfined compressive strength. Since an increase in plastic viscosity results in an increase in unconfined compressive strength [26], and the fact that the yield value is generally taken as half the unconfined compressive strength [27], it can be concluded that the yield value is influenced in a direct proportional relationship by the plastic viscosity, which is in agreement with the concept suggested by Equation 6. However, when the particle sizes are changed, the same output unconfined compressive strength value is obtained for the much lower value of plastic viscosity [14].…”
Section: Sensitivity Analysis Of Parameters Related To Bi-viscosity M...supporting
confidence: 81%
See 3 more Smart Citations
“…Next, to deduce the relationship between plastic viscosity and the yield value, it is important to notice the relation between plastic viscosity and the unconfined compressive strength. Since an increase in plastic viscosity results in an increase in unconfined compressive strength [26], and the fact that the yield value is generally taken as half the unconfined compressive strength [27], it can be concluded that the yield value is influenced in a direct proportional relationship by the plastic viscosity, which is in agreement with the concept suggested by Equation 6. However, when the particle sizes are changed, the same output unconfined compressive strength value is obtained for the much lower value of plastic viscosity [14].…”
Section: Sensitivity Analysis Of Parameters Related To Bi-viscosity M...supporting
confidence: 81%
“…For soil containing a low water content, the repulsive electrostatic force is high [35]. Considering the low water content and higher particle distance in the samples used in this simulation, it was assumed that the influence of surface tension would be for the unconfined compression tests of the soil samples, as they would remain in the rigid state of the bi-viscosity model [26]. Thus, the calculation of surface tension is omitted in this study by assigning the calculation method as none.…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…The adoption of the Moving Particle Simulation (MPS) method with Computer Aided Engineering (CAE), that is MPS-CAE simulation in geotechnical engineering represents a significant step towards more sustainable construction practices [76][77][78][79][80][81][82][83][84][85][86]. In particular, Inazumi et al [14] innovatively applied MPS-CAE simulation to analyze and elucidate the intricate construction mechanisms underlying jet grouting technology.…”
Section: New Innovative Mps-cae Simulationmentioning
confidence: 99%